P279 Distribution of single unit activity patterns in subthalamic nucleus of Parkinsonian patients. Issue 9 (September 2017) - Belova, Elena; Nezvinskiy, Artem; Semenova, Ulia; Usova, Svetlana; Popov, Valentin; Gamaleya, Anna; Tomskiy, Alexey; Sedov, Alexey
Abstract : Objectives: Subthalamic nucleus (STN) is the main target for surgery treatment of Parkinson's disease (PD) patients. The aim of the study was to characterize spontaneous single unit activity in subthalamic nucleus of PD patients and to search for the possible correlations between characteristics of neuronal activity and clinical phenotype. Methods: We have analyzed single unit activity of 493 cells registered in subthalamic nucleus of 9 patients (3 males and 6 females) with PD (56.8 ± 4.8 yrs, UPDRS III score in off-state 52.0 ± 12.2), that were undergoing bilateral DBS surgery at Burdenko Neurosurgery Center in 2015–2017. For each neuron we determined several characteristics: firing rate, coefficient of variation (CV), mean and median interspike interval (ISI), asymmetry index (AI), burst characteristics. We also have performed spectral analysis of oscillations in the spiketrains. Results: We have identified three different patterns of neuronal activity: tonic regular activity (AI > 0.7, CV < 0.85) was present in 5–16% of neurons, tonic irregular activity (AI > 0.7, CV > 0.85)? in 5–25% of neurons, burst-like activity (AI < 0.7)? in 55–90% of neurons. There was unevenness in pattern distribution across STN: tonic neurons were located mainly in ventral part of STN, irregular neurons also were met more frequently in ventral segments of STN. Unlike tonic units, burst-like neurons were distributed more evenly, however, there is a tendency in AI scores of bursts-like neurons to increase with increasing distance from STN entrance. Spectral analysis have shown that beta oscillation activity was observed mainly in dorsal STN segment whereas gamma oscillation activity was seen predominantly in ventral part of STN. We found that characteristics of tonic regular neurons varied significantly across examined patients. We haven't found any clear correlations between characteristics of different types of neurons and clinical symptoms of PD (UPDRS score, bradykinesia, rigidity or tremor scores). Significance: The unevenness of neuronal activity patterns and oscillations of STN could be used for choosing optimal location of DBS electrodes in PD patients.